Digital Transformation In Nursing Management: A Systematic Literature Review Of Leadership, Technology Integration, And Patient-Centered Care - Rince Aida Rostika; Mageswaran Sanmugam; Muhammad Adamu Abubakar; Eko Risdianto; Mohammad Qais Rezvan (CV Media Inti Teknologi, 2025)
Background: Digital transformation has become a critical driver in improving healthcare quality, efficiency, and accessibility, particularly within nursing management. However, existing studies often examine technology adoption, leadership, and patient-centered care separately, resulting in fragmented understanding of their interrelationships in nursing management contexts.Objective:This study aims to synthesize evidence on how digital transformation is implemented in nursing management, examine the role of nursing leadership in technology integration, and evaluate its impact on patient-centered care and clinical decision-making.Method: A Systematic Literature Review (SLR) was conducted following PRISMA 2020 guidelines using the Scopus database for publications from 2001–2025. Search strategies combined keywords related to digital transformation, nursing management, leadership, health informatics, and patient-centered care. From 323 records, 75 studies met inclusion criteria after screening, eligibility assessment, and full-text review. Bibliometric analysis was performed using Biblioshiny and VOSviewer to identify trends and thematic networks.Result: Findings indicate that technologies such as electronic health records (EHR), telemedicine, artificial intelligence (AI), and clinical decision support systems significantly enhance service accessibility, personalization, and patient engagement. Nursing leadership plays a pivotal role in aligning technological innovations with clinical workflows, managing organizational change, and addressing risks related to data security and digital competency gaps. Nevertheless, challenges persist, including administrative burden, alert fatigue, privacy concerns, and uneven digital readiness among nurses.Conclusion: Digital transformation in nursing management is a multidimensional process requiring strong, adaptive leadership and strategic integration of technology to achieve sustainable patient-centered care. This review proposes an integrative perspective linking leadership, digital systems, and clinical outcomes, and highlights future research needs in longitudinal evaluation, contextual validation, and socio-ethical impacts of digital healthcare transformation.